HELIUM AND NEON ISOTOPIC EVIDENCE FOR LOWER MANTLE CONTRIBUTION TO THE TERCEIRA ISLAND MAGMATISM - Madureira, Pedro (2011)
The Azores archipelago, located close to the triple junction where the Eurasian, African and American plates meet, is an example of plume related magmatism. Mantle plumes have been the locus of an intense debate. Their ultimate origin has been assigned to the D” layer, to the bottom of transition zone and even to the astenosphere, as the result of passive response to lithosphere cracking (e.g. Courtillot et al., 2003). He isotope geochemistry is a key tool to clear up this question given its ability to identify the incorporation of relatively undegassed lower mantle portions in plumes (with 4He/3He ratios as low as 20.000 or R/Ra=32) and to distinguish them from those generated in a degassed upper mantle generally accepted as the MORB source (with constant 4He/3He ratios around 90.000 or R/Ra8; e.g. Allègre et al., 1995). More recently, it has been demonstrated that the two mantle reservoirs expected from helium isotope systematics can be substantiated by neon data (Moreira et Allègre, 1998). In this work we present the first Ne isotopic data collected from Terceira samples; these data, in addition to new He isotope determinations, are used to better constrain the origin of the Azores mantle plume. The noble gases analyses were performed at IPG in Paris by crushing of olivine phenocrysts (~1g). This method is particularly useful for measuring the mantle gases released by melt inclusions trapped inside the olivine crystals. Terceira island comprises four main strato-volcanoes (Self, 1976): Cinco Picos, Guilherme Moniz, Pico Alto and Santa Bárbara. At least the later two are considered to be active and connected by a fissure zone regarded by some authors as the Terceira rift (e.g. Udías, 1980). One of the oldest features of the island is expressed by the Cinco Picos caldera (7 km in diameter) that should be younger than 300.000 years (K/Ar data from Feraud et al., 1980). Previous studies have shown that Terceira lavas combine relatively high radiogenic lead isotopic signatures typical from HIMU basalts (206Pb/204Pb up to 20.02) and slight primitive He signatures, with 63780 as a minimum value of 4He/3He ratio (R/Ra=11.3; Dupré et al., 1982; Moreira et al., 1999). A lower value of 48821 (R/Ra=14.8) was now obtained, strengthening the contribution of lower mantle to Terceira magmas. Our results also suggest a stratigraphic control on the variation of He isotopic signatures since the most primitive values appear to be confined to the most ancient rocks. In fact, values lower than 68814 (R/Ra ratios higher than 10,5) were found in one lava collected near the village of Säo Sebastiäo (SE of Terceira, in one of the most eroded landscape of the island) and in samples from the lower levels of a 20 m thick lava flow sequence exposed in the actual sea cliff near the village of Santa Bárbara (SW of Terceira). At least for the later samples, we exclude the possibility of a cosmogenic 3He contribution since this sequence is exposed in a relatively recent erosion surface. Our results raise important questions concerning the evolution of the Açores plume; several interpretations seems to be plausible, as the changing with time of the source isotopic signature or the increase of mixing with a MORB. These hypothesis will be better constrained in future works. Some of the analysed samples show higher 20Ne/22Ne and 21Ne/22Ne ratios than air suggesting the presence of a mantle component in the olivine melt inclusions. Moreover, in a three-Ne isotope diagram, the samples define a trend with a higher slope than the MORB line (e.g. Sarda et al., 1988). The Terceira trend is then interpreted as a mixing line between an atmospheric component and a mantle component with a solar like 20Ne/22Ne ratio and with a 21Ne/22Ne ratio of 0.052 (extrapolated to solar). This value is in accord with the mantle mixing model predicted by the 4He/3He-21Ne/22Ne relationship (Moreira et al.,2001) and is also strongly suggestive of a lower mantle contribution to Terceira magmas.